2006
DOI: 10.1002/chin.200652188
|View full text |Cite
|
Sign up to set email alerts
|

Momordica charantia Constituents and Antidiabetic Screening of the Isolated Major Compounds.

Abstract: Terpenes U 0200Momordica charantia Constituents and Antidiabetic Screening of the Isolated Major Compounds. -Three new cucurbitane triterpenoids (I) and 8 known compounds are isolated from the methanol extract. The antidiabetic effect of the isolated major constituents is screened. The aglycon of (Ic) significantly decreases the blood glucose levels. -(HARINANTENAINA, L.; TANAKA, M.; TAKAOKA, S.; ODA, M.; MOGAMI, O.; UCHIDA, M.; ASAKAWA*, Y.; Chem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
37
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 1 publication
2
37
0
3
Order By: Relevance
“…Bitterness of fruit is controlled by a single gene, with more bitterness dominant to less (Suribabu et al, 1986). Saponins, momordicosides K and L, as well as momordicines I and II cause the bitter taste (Harinantenaina et al, 2006).…”
mentioning
confidence: 99%
“…Bitterness of fruit is controlled by a single gene, with more bitterness dominant to less (Suribabu et al, 1986). Saponins, momordicosides K and L, as well as momordicines I and II cause the bitter taste (Harinantenaina et al, 2006).…”
mentioning
confidence: 99%
“…Studies have tested new drugs for the treatment of skin wounds in patients with DM in an attempt to minimize inflammation and to accelerate the repair process by increasing the production of fibroblasts and collagen fibers, factors that are important for wound healing 9 . Medicinal plants such as Strychnos pseudoquina…”
Section: Introductionmentioning
confidence: 99%
“…and Momordica charantia have been used for the treatment of DM as coadjuvants in the anti-inflammatory process 9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…The phytochemical studies reported earlier indicate that alkaloids, steroids and steroidal lactones isolated from other plant sources are responsible for their hypoglycemic activity (Sofowora 1982;Adebajo et al 2006;Hrinantenaina et al 2006;Pries et al 2006;Veiga et al 2006). A number of steroidal lactones have also been reported from W. coagulans (Ramaiah et al 1984;Choudhary et al 1995;Rahman et al 1998Rahman et al , 1999Nur-e-Alam et al 2003).…”
mentioning
confidence: 97%